(untitled) (Global Journal of Science Frontier Research, 2023)
The study investigated the water quality of the Nale-rigu dam and compared to the WHO recommended levels for both physicochemical and bacteriological parameters. There was also a survey of 99 out of 135 household heads who were within 50 meters around the dam to assess their usage of the dam water. The sampled dam water was analysed at the Water Research Institute laboratory in Tamale. The water pH was found to range from 6.30 to 6.50 with a mean temperature range of 30.3 to 30.50C. The turbidity of the water exceeded the WHO limits. Other physicochemical parameters monitored including total suspended solids, total dissolved solids, total hardness, total alkalinity values were within the WHO recommended levels for surface water quality. Results of the bacteriological analysis including faecal coliforms and total coliforms were high. It was concluded that the Nalerigu dam was contaminated and unsafe for human consumption if not treated. The study recommends a further study into metallic concentration of the dam to ensure the quality besides physicochemical and bacteriological parameters of the dam.